Power Plant for a 0.60.8 Class Mobile Vehicle Based on the T16 SelfPropelled Tractor Chassis - V. A. Gusarov (Сельскохозяйственные машины и технологии)
The authors showed the necessity to develop a rear-wheel drive hybrid mobile agricultural vehicle with electric drive and power plant. (Research purpose) To develop and study a new kinematic scheme of a mobile vehicle based on a self-propelled tractor T-16 chassis, which provides increased reliability, comfortable working conditions for the operator, a significant improvement in the environmental situation, and better economic efficiency. (Materials and methods) The authors listed the advantages of the new hybrid vehicle kinematic scheme. They gave the comparative technical characteristics of a diesel engine and an asynchronous electric motor. They developed a new methodology for calculating gas turbine engine technical parameters and described the production process of an electric drive with a capacity of 11 kilowatts to drive the driving wheels. The authors gave a thermal design of the compressor parameters, turbine. They calculated the excess air ratio. According to the parameters obtained, a K27-145 turbocharger was chosen, which simultaneously served as a turbine and a compressor of a gas turbine engine. A kinematic diagram was created with a gas turbine electric generator, storage batteries, an asynchronous frequency-controlled motor and a mechanical gearbox. (Results and discussion) The authors proposed to use a mobile vehicle as a mobile power plant: an output socket with a voltage of 220-230 volts operated from an inverter connected to batteries; the second socket – with a three-phase voltage of 400 volts – from the generator of the power gas turbine plant. (Conclusions) It was proved that the proposed hybrid mobile vehicle design on a battery and a gas turbine was capable of operating throughout the entire working day, and to provide 16 horsepower of a diesel engine, it was enough to install an asynchronous electric motor with a capacity of 7.5 kilowatts. The authors calculated the compressor performance of the gas turbine engine, which was 0.178 kilograms per second. The geometric parameters of the combustion chamber and the technical characteristics of the turbocharger were determined.